Integrative Production Technology Theory and Applications - Brecher, Christian; Özdemir, Denis (Springer International Publishing : Imprint: Springer, 2017)
This contributed volume contains the research results of the Cluster of Excellence "Integrative Production Technology for High-Wage Countries", funded by the German Research Society (DFG). The approach to the topic is genuinely interdisciplinary, covering insights from fields such as engineering, material sciences, economics and social sciences. The book contains coherent deterministic models for integrative product creation chains as well as harmonized cybernetic models of production systems. The content is structured into five sections: Integrative Production Technology, Individualized Production, Virtual Production Systems, Integrated Technologies, Self-Optimizing Production Systems and Collaboration Productivity.The target audience primarily comprises research experts and practitioners in the field of production engineering, but the book may also be beneficial for graduate students. .